Action of decoquinate in altering feed efficiency of ruminants - D.L. Harmon (Kansas Agricultural Experiment Station Research Reports, 1985)
The effects of adding decoquinate (Deccox®) to the diet at 0, 0.5, or 5 mg per kg body weight were evaluated with diets of 30 and 80% concentrate. Decoquinate did not influence rumen or plasma metabolites, diet digestibility, or volatile fatty acid production. No metabolic effects were seen that would suggest a role for decoquinate in altering rumen fermentation and feed efficiency of ruminants.
Keywords: Cattlemen& #x27; s Day; 1985; Kansas Agricultural Experiment Station contribution; no. 85-319-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 470; Beef; Feed efficiency; Decoquinate; Digestibility; Fermentation